New species of Salicaceae with opposite leaves from the Atlantic Forest, Brazil - Nepomuceno, Álvaro; Domínguez, Yoannis [UNESP]; Negrão, Raquel; Nichio Amaral, Renara; Dutra, Valquíria Ferreira; Alves-Araújo, Anderson (Magnolia Press, 2024)
Abatia mantiqueirensis is described and illustrated as a new species with distribution for the Brazilian states of Minas Gerais and Rio de Janeiro. It is morphologically similar to A. americana but can be distinguished by the presence of canaliculated petiole, acute serrate leaf margin, glands at the apex of the margin serrations that are rounded to concave and projected outwards from the leaf blade, upper portion of the pedicel winged and seeds with tiny dorsal wings. Taxonomic description, comments, and geographical distribution information are here in provided. So far, only three populations of A. mantiqueirensis are known with only one of them recorded in a protected area. Based on the availability of suitable habitats, possible threats and future potential geographical distribution, we propose the conservation status for A. mantiqueirensis as Critically Endangered.
Keywords: Abatia; conservation; endemism; Flacourtiaceae; Mantiqueira mountain; mountain forest